Podstawy prawne ochrony tajemnicy pracodawcy w służbie publicznej - Szpor, Grażyna (Kwartalnik Prawa Publicznego, 2012)
Labour code is an autonomous basis for the protection of employer’s confidentiality, including refusal to reveal information that could potentially harm the employer, which is not subject to separate regulations of confidentiality. Acts on: employees of state authorities, act on public service and act on foreign service, take precedence over the labour code with regard the protection of the employer’s confidentiality and other laws that protect confidentiality. Auxiliary application of labour code may provide a basis for requiring such confidentiality from employees of self-government, employees of courts and prosecutors’ offices. Regulations on employer’s confidentiality with regard to different categories of public sector employees are scattered, inconsistent, and non-transparent, which should lead to their review and amendments.